Monitoring of a galvanized metal water tank at Unimas temporary campus by using acoustic emission: a case study - Chieng, S.M (University Malaysia Sarawak (UNIMAS), 2003)
This research project looks into the detection of internal activities such as cracks, corrosion, dislocation of atoms, fatigue, diffusion, etc. of a galvanized metal water tank by using one of the non-destructive methods, namely "Acoustic Emission". In this research project, acoustic emission monitoring work was carried out at the different locations of the structure. Internal activities of the structure were subsequently determined based on counts vs time, counts vs amplitude and energy vs amplitude.